STEREOLOGY: A HISTORICAL SURVEY - Cruz-Orive, Luis Manuel (Image Analysis and Stereology, 2017)
Stereology is the science of geometric sampling, with applications to the statistical analysis of microstructures in biology and materials science. Subsidiary disciplines are image analysis, quantitative microscopy, and radiology. This survey is organized chronologically within a series of topics which cover most aspects of stereology. Each topic is described informally to make it accessible to scientists of different disciplines.